Comparison of the effects of magnesium sulphate and dexmedetomidine on surgical vision quality in endoscopic sinus surgery: randomized clinical study - Akkaya,Akcan (2014)
Background and objectives: Even a small amount of bleeding during endoscopic sinus surgery can corrupt the endoscopic field and complicate the procedure. Various techniques, including induced hypotension, can minimize bleeding during endoscopic sinus surgery. The aim of this study was to compare the surgical vision quality, haemodynamic parameters, postoperative pain, and other effects of magnesium, a hypotensive agent, with that of dexmedetomidine, which was initially developed for short-term sedation in the intensive care unit but also is an alpha 2 agonist sedative. Method: 60 patients between the ages of 18 and 45 years were divided into either the magnesium group (Group M) or the dexmedetomidine group (Group D). In Group M, magnesium sulphate was given at a pre-induction loading dose of 50 mg kg−1 over 10 min and maintained at 15 mg kg−1 h−1; in Group D, dexmedetomidine was given at 1 mcg kg−1 10 min before induction and maintained at 0.6 mcg kg−1 h−1. Intraoperatively, the haemodynamic and respiratory parameters and 6-point intraoperative surgical field evaluation scale were recorded. During the postoperative period, an 11-point numerical pain scale, the Ramsay sedation scale, the nausea/vomiting scale, the adverse effects profile, and itching parameters were noted. Results: Group D showed a significant decrease in intraoperative surgical field evaluation scale scale score and heart rate. The average operation time was 50 min, and Group M had a higher number of prolonged surgeries. No significant difference was found in the other parameters. Conclusions: Due to its reduction of bleeding and heart rate in endoscopic sinus surgery and its positive impacts on the duration of surgery, we consider dexmedetomidine to be a good alternative to magnesium.